ORGANIZATIONAL CHARACTERISTICS, ENVIRONMENT UNCERTAINTY & CONSTRUCTION INNOVATION: EVIDENCE FROM MALAYSIAN CONSTRUCTION INDUSTRY - Hasnan, Norlena; Seng, Ng Weng; Mohtar, Shahimi; Osman, Nor Hasni; Abidin, Rahimi (CENTRAL ASIA AND THE CAUCASUS, 2021)
Constructions industry has increasingly becoming more dynamic, demanding the adoption of innovative methods, and greater technological advancement. The complexity of the industry, generally has been described as multi-faceted and highly fragmented with significant problems such as communication breakdown, conflicts, and disputes. The uniqueness of projects, the organization itself and the management role in coping the changing demands can apparently influence the effort in adopting the new technologies and innovation in the construction sector. In addition, the construction environment which is known as dynamic and full with uncertainties posed difficulty for the management to understand their organization's ability to function in the future. Hence, this paper interested to identify the effects of organizational characteristics and the perceived level of environmental uncertainties towards the implementation of construction innovation. In order to fulfill the research objectives, online survey has been conducted among the construction companies in Malaysia. The on-line questionnaires have been send to randomly selected contraction companies that operating in Malaysia and registered as G7 contractor with CIDB. The number of returned questionnaires was totaled to be 383, yielding an effective response rate of 54.4%. The result showed all the variables proposed have been foundto be positively correlated with construction innovation. Apart from suggesting the direction of future construction industry study, this paper is valuable in providing insights for the contractors in implementing innovative construction technologies that can be used to devise strategic marketing plans and ultimately for enjoyment of the competitive advantages.